3D printing of foetal vascular rings: feasibility and applicability - Jia Huang; Hao Wang; Yuanting Yang; Qian Chen; Jiaqi Hu; Hua Shi; Qing Zhou (BMC, 2023)
Abstract Background Vascular rings (VRs) exhibit complex and diverse forms that are difficult to conceptualize using traditional two-dimensional (2D) schematic. Inexperienced medical students and parents who lack a medical technology background face significant challenges in understanding VRs. The purpose of this research is to develop three-dimensional (3D) printing models of VRs to provide new technical imaging support for medical education and parental consultation. Methods This study included 42 fetuses diagnosed as VRs. Foetal echocardiography, modeling and 3D printing were performed, and the dimensional accuracy of models was analyzed. The value of 3D printing in the teaching of VRs was analyzed based on comparing the test results before and after the teaching intervention of 48 medical students and the satisfaction survey. A brief survey was conducted to 40 parents to assess the value of the 3D printed model in prenatal consultations. Results Forty models of VRs were successfully obtained, which reproduced the anatomical shape of the VRs space with high dimensional accuracy. No differences in the prelecture test results were noted between the 3D printing group and the 2D image group. After the lecture, the knowledge of both groups improved, but the postlecture score and the change in the prelecture versus postlecture score were greater in the 3D printing group, and the subjective satisfaction survey feedback in the 3D printing group was also better (P < 0.05). Similar results were observed from the parental questionnaire, the vast majority of parents have an enthusiastic and positive attitude towards the use of 3D printed models and suggest using them in future prenatal consultations. Conclusions Three-dimensional printing technology providing a new tool for effectively displaying different types of foetal VRs. This tool helps physicians and families understand the complex structure of foetal great vessels, positively impacting medical instruction and prenatal counselling.